2022
DOI: 10.1002/app.53143
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reinforced polymer composites: An opportunity to recycle plastic wastes and their future trends

Abstract: Polymers and their composites have played an important role in industrial development. Polymer composites are becoming much stronger and more competitive than other materials as a result of ongoing research and development. This was made possible by newly developed techniques that could alter the physical and chemical properties of constituents. One of them is the self‐reinforcement technique, which allows for the fabrication of high‐strength thermoplastic polymer composites with reserved degradability, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 121 publications
0
12
0
Order By: Relevance
“…Incorporating long natural fibers, such as jute, as reinforcements in thermoplastics has environmental advantages, improved mechanical properties, lower weight, and higher cost effectiveness. Recycling cellulose-filled thermoplastic composites is also simpler and more cost-efficient than recycling composites reinforced with inorganic fillers [17,18]. However, cellulose materials have limitations in mass production and industrial use because of the poor bonding between the cellulose fiber and the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating long natural fibers, such as jute, as reinforcements in thermoplastics has environmental advantages, improved mechanical properties, lower weight, and higher cost effectiveness. Recycling cellulose-filled thermoplastic composites is also simpler and more cost-efficient than recycling composites reinforced with inorganic fillers [17,18]. However, cellulose materials have limitations in mass production and industrial use because of the poor bonding between the cellulose fiber and the polymeric matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites reinforced by carbon and glass fibers have been widely utilized in many engineering fields including aerospace aircrafts, wind turbine blades, and automotive industries due to their high strength and stiffness, outstanding wear resistance, long service life, and excellent corrosion/fire resistance, and so forth 1–3 . Nonetheless, the broad applications of fiber reinforced polymer (FRP) composites have accompanied the significant quantities of waste, which leads to a huge energy consumption and a series of environmental problems 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites reinforced by carbon and glass fibers have been widely utilized in many engineering fields including aerospace aircrafts, wind turbine blades, and automotive industries due to their high strength and stiffness, outstanding wear resistance, long service life, and excellent corrosion/fire resistance, and so forth. [1][2][3] Nonetheless, the broad applications of fiber reinforced polymer (FRP) composites have accompanied the significant quantities of waste, which leads to a huge energy consumption and a series of environmental problems. 4,5 As reported, over 6000 civil aviation aircrafts will be decommissioned by 2030 6 and it was also predicted that about 43 million tons of turbine blade wastes would be generated worldwide by 2050, 7 where there would be huge amounts of FRP composite wastes in the world that require to be treated properly.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber reinforcements can be glass fiber, carbon fiber and metal fiber, and so forth, and they vary from short fiber, long fiber to continuous fibers in composite materials. [17][18][19][20][21] The earlier studies found that the mechanical properties of fiber reinforced thermoplastic composite materials are highly depends on the fiber length, and generally the longer length of the fiber, the higher mechanical properties of the thermoplastic composites. 22,23 Therefore, researchers normally prefer the longest length of fiber in the thermoplastic composites, especially for those thermoplastic composites used as structural materials requiring high mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber reinforced thermoplastic composites is a big category of thermoplastic composite materials, which has been developing for half a century so far this year. The fiber reinforcements can be glass fiber, carbon fiber and metal fiber, and so forth, and they vary from short fiber, long fiber to continuous fibers in composite materials 17–21 . The earlier studies found that the mechanical properties of fiber reinforced thermoplastic composite materials are highly depends on the fiber length, and generally the longer length of the fiber, the higher mechanical properties of the thermoplastic composites 22,23 .…”
Section: Introductionmentioning
confidence: 99%